Role of octreotide and instillation of povidone-iodine in the treatment of lymphorrhea in renal transplantation: A comparative study - Vaibhav Kant Baderiya; Dilip Kumar Pal; Atanu Pal (Indian Journal of Transplantation, 2024)
Background: Lymphorrhea is a minor complication after kidney transplantation but may develop into a lymphocele and prolong hospital stay. Treatment is conservative based on percutaneous drainage until lymphatic leakage cessation. It has been reported that povidone iodine instillation and octreotide has beneficial effects to treat lymphorrhea after renal transplantation. Aims and Objectives: The aim of this study was to compare the povidone iodine instillation and octreotide treatment in lymphorrea after kidney transplantation. To evaluate the efficacy of povidone iodine and octreotide injection in comparison to control group for the treatment of lymphorrhea in renal transplant patient. Materials and Methods: It was comparative analytical study included 60 recipients of both cadaveric and live kidney allografts with posttransplant lymphorrhea including 20 treated with instillation of betadine solution, 20 with octreotide (0.1 mg three times a day subcutaneously), and 20 was control group (no betadine and octreotide was used). We reviewed the daily amount of fluid collection, duration of lymphorrhea, complications, lymphocele formation, rejection episodes, graft outcomes, and hospital stay. Results: The average duration of lymphorrhea was (8.85 ± 0.88) and (11.6 ± 0.94) and (16.15 ± 0.81) days for the betadine groups, the octreotide groups and control groups respectively. (P < 0.05) . No lymphoceles occurred among the betadine group, while three lymphoceles were found among patients treated with octreotide and five lymphocele were found among control groups. No differences were observed for wound infection, graft dysfunction episodes or renal function and death between the groups. No octreotide and povidone related adverse events were noted. Conclusion: The mean length of lymphorrhea was lower with povidone iodine instillation as compared to octreotide treatment. There was a shorter hospital stay and minor patient discomfort in betadine groups. In conclusion, lymphatic leakage after kidney transplantation may be successfully managed by betadine instillation as compared to octreotide and control groups.